SPATIAL DISTRIBUTION OF METALS IN URBAN TOPSOILS OF XUZHOU (CHINA): CONTROLLING FACTORS AND ENVIRONMENTAL IMPLICATIONS - Wang X.; Qin Y. (My University, 2006)
The contamination of soils by metals from various sources is a subject of increasing concern in recent times. Twenty-eight elements (Fe, Ti, Cr, Al, Ga, Pb, Sc, Ba, Li, Cd, Be, Co, Cu, Mn, Ni, V, Zn, Mo, Pt, Pd, Au, As, Sb, Se, Hg, Bi, Ag and Sn) have been analyzed from urban topsoil from the city of Xuzhou. The concentrations of these analyzed elements have been correlated to some soil parameters such as organic matter, pH, cation exchange capacity, carbonate content, and granulometric fractions (clay, silt and sand). Results of the statistical analysis show a large variety and complexity in these relationships. The spatial distributions of these metal concentrations were also constructed using geographical information system. The spatial distribution patterns of the elements analyzed show that traffic and industrial activities are the principal anthropogenic pollutant sources.
Keywords: URBAN TOPSOILS; HEAVY METAL; GIS; SPATIAL DISTRIBUTION; SOIL CONTAMINATION; CHINA